2019
DOI: 10.1155/2019/2834019
|View full text |Cite
|
Sign up to set email alerts
|

Study on Compaction of Reclaimed Soil of Nonmetallic Mining Area in Northern Foothills of Tianshan Mountains in Xinjiang, China

Abstract: This study focused on the changes of the compaction of the reclaimed soil after the reclamation process and the one-year maintenance period of the nonmetallic mines in north foothills of Tianshan Mountains in Xinjiang. The plate load experiment method was employed to simulate the compaction effect of various times of compaction from the reclamation machine on a different thickness of the reclaimed soil. The experimental data were analyzed by multivariate statistical analysis. The experimental results showed bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The significant changes in their hydraulic conductivity attributed to the decreases in porosity upon compaction. Previous study reported the differences in porosity of mine wastes compacted under different compactive energy [12]. Similarly, in a microstructure and porosity study using analytical permeability model, it was observed that various degrees of compaction (85, 95, 100, and 105%) affects the morphological parameters of the porous network [13].…”
Section: Effects Of Degree Of Compactionmentioning
confidence: 82%
“…The significant changes in their hydraulic conductivity attributed to the decreases in porosity upon compaction. Previous study reported the differences in porosity of mine wastes compacted under different compactive energy [12]. Similarly, in a microstructure and porosity study using analytical permeability model, it was observed that various degrees of compaction (85, 95, 100, and 105%) affects the morphological parameters of the porous network [13].…”
Section: Effects Of Degree Of Compactionmentioning
confidence: 82%
“…e water content was generally higher at a depth of 30 cm. e physical properties of the reconstructed soil at the early stage [24] show that the fine particle content at this depth was generally lower than that of the other soil depths, and the porosity was generally large [25], which provided space for the storage of water.…”
Section: Water Distribution In Covering Soil With a Ickness Of 70 CMmentioning
confidence: 97%
“…Recently, studies on the soil compaction have yielded fruitful results, such as the effect of compaction on water infiltration in soil [1], the changes of physical and chemical properties of the reclaimed soil after compaction [2][3][4][5][6][7][8][9], the effect of using different reclamation materials on the soil compaction [10][11][12], the impact of compaction on the water content of soil [13][14][15][16][17][18][19], the effect of compaction on the soil structure [20,21], and the effect of different compaction conditions on porosity of reclaimed soil [22]. According to the previous research results, it was found that studies on the compaction of soil were mostly concentrated on the agricultural field, and the compaction studies of the reclaimed soil in the mining area were mostly focusing on the soil reclamation in the coal mining area.…”
Section: Introductionmentioning
confidence: 99%